Effects of incubation temperatures on embryonic and larval survival in rainbow trout, Oncorhynchus mykiss. Issue 4 (1st October 2016) - Weber, Gregory M.; Martin, Kyle; Kretzer, Joshua; Ma, Hao; Dixon, Douglas
ABSTRACT: Incubation temperature is commonly used to manipulate hatch date in salmonids. Although rapid adjustments in temperature are required to meet target dates, there is little information available on the effects of such changes on embryo survival. We compared the effects of temperature treatments on survival at ~250 degree days (considered eyeing), calculated as the sum of mean daily water temperature in degrees Celsius, and at first feeding. Incubation at 5°C within the first day of fertilization reduced survival at eyeing compared to incubation at 10°C or 14°C. Survival at eyeing or first feeding did not differ between embryos rapidly switched between 5°C and 10°C at 100 degree days, and embryos acclimated to the change in temperature over a 4-h period. Switching embryos from 10°C to 2°C at 100 degree days reduced survival at eyeing and first feeding by about 14% and 18% respectively, although there were differences among studies. The more time spent incubating at suboptimal temperatures, 14°C, 5°C, or 2°C, versus at 10°C, the greater the impact on survival with more extreme temperatures such as 2°C compared with 5°C having a greater impact. These impacts can be minimized if the low temperatures are avoided for the first day of incubation and perhaps avoiding temperatures near or in excess of 2°C.